KRITIK MATAN TENTANG HADIS–HADIS SEMBELIHAN AQIQAH - Siregar, Dame (IAIN Padangsidimpuan, 2013)
Hadist of aqiqoh is not found in Al-Qur’an and it is a kind of cutting animal in Zahiliah as representation of qurban in Adam and Ibrahim Prophets. The Hadist is always contra between on and another where the hadists are sohih on its quality. The Hadist is contra with siroh Nabi Muhammad (PBUH). So, hadist on aqiqah has been mansukh and empowered by hadist forbiding Fatimah and Ali bin Abu Tolib to give aqiqoh on Hasan dan Husain.